Tanggung Jawab Hukum Lembaga Keuangan Syariah terhadap Cyber Crime: Pendekatan Sadd az-Zari'ah - Muhammad Firdaus; Zulqarnain Zulqarnain; Fakhrurrazi Fakhrurrazi; Alvi Suliya; Alif Mahfudz (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to analyze the legal responsibility of Islamic financial institutions in addressing cybercrime, examine the implementation of the Sadd al-Dharī'ah principle as a preventive approach to digital security governance, and formulate a conceptual model for customer protection and rights recovery. This research employs a qualitative library research method using a normative legal approach, incorporating statutory, conceptual, and Islamic legal perspectives. Data were analyzed through descriptive-analytical techniques based on primary and secondary legal sources. The findings reveal that the legal responsibility of Islamic financial institutions should integrate the principles of amanah (trustworthiness), ḥifẓ al-māl (protection of property), national legal regulations, and Sadd al-Dharī'ah as a preventive framework against cybercrime. Furthermore, this study proposes a customer protection model consisting of preventive measures, detection mechanisms, responsive actions, and recovery procedures as an integrated framework for digital security governance that is adaptive, accountable, and aligned with the objectives of Islamic law (maqāṣid al-sharīʿah).